Mechanisms regulating angiogenesis underlie seasonal control of pituitary function - Castle-Miller, Jennifer; Bates, David O.; Tortonese, Domingo J. (National Academy of Sciences, 2017)
Seasonal changes in mammalian physiology, such as those affecting reproduction, hibernation and metabolism, are controlled by pituitary hormones released in response to annual environmental changes. In temperate zones, the primary environmental cue driving seasonal reproductive cycles is the change in daylength (photoperiod), encoded by the pattern of melatonin secretion from the pineal gland. However, although reproduction relies on hypothalamic gonadotrophin-releasing hormone (GnRH) output, and most cells producing reproductive hormones are in the pars distalis (PD) of the pituitary, melatonin receptors are localized in the pars tuberalis (PT), a physically and functionally separate part of the gland. How melatonin in the PT controls the PD is not understood. Here we show that melatonin time-dependently acts on its receptors in the PT to alter splicing of vascular endothelial growth factor (VEGF). Outside the breeding season, angiogenic VEGF-A stimulates vessel growth in the infundibulum, aiding vascular communication between the PT, PD and brain. This also acts on VEGFR2 expressed in PD prolactin-producing cells known to impair gonadotrophin secretion. In contrast, in the breeding season, melatonin releases anti-angiogenic VEGF-Axxxb from the PT, inhibiting infundibular angiogenesis and diminishing lactotroph VEGFR2 expression, lifting reproductive axis repression in response to shorter day lengths. The time-dependent, melatonin-induced differential expression of VEGF-A isoforms culminates in alterations in gonadotroph function opposite to those of lactotrophs, with up-regulation and down-regulation of gonadotropin gene expression during the breeding and non-breeding season, respectively. These results provide a novel mechanism by which melatonin can control pituitary function in a seasonal manner.